Insuffisance Rénale Aigue Obstétricale : Expérience De La Maternité Issaka GAZOBY De Niamey (Niger) - Tondi, Zeinabou Maiga Moussa; Nayama, Madi; Kane, Yaya; Garba, Moumouni; Lemrabott, Ahmet Tall; Moussa, Hassane Diongoulé; Abdou, Idé; Yogo, Epiphanie .C Magni (European Scientific Journal, ESJ, 2016)
Introduction Acute renal failure (ARF) is a serious obstetric complication of pregnancy, a real health problem in developing countries. It is more related to the pathologies of pregnancy affecting the mother rather than the fetus. The purpose of our study was to assess sociodemographic, clinical, therapeutic and evolutionary features in obstetric acute renal failure. Materials and Methods: A cross sectional study of 6 months (August 2015- January 2016) was conducted. The study involved pregnant women over 20- week amenorrhea including the immediate postpartum admitted for acute renal failure. Results: Thirty-two patients were involved. The mean age was 25.21 ± 5.14 years. Most of them were first-time mothers (53.1%). Surrounding hospital exits account for 71.9% of the admissions. 31.25% (N = 10) of the patients did not receive any antenatal care. The main clinical signs at admission were hypertension (86.6%), oliguria (40.5%) and edema syndrome (37.5%). Eclampsia and severe pre-eclampsia represented the causes of the ARF in 68.75% cases. Considering 8 patients (25%) who were supposed to undergo dialysis therapy, only one took the treatment. The average hospital stay was 15.20 ± 7.45 days. Renal function resolved in 68.75% of patients and 15.62% developed chronic renal sequelae. At the end of the study, we recorded 5 cases of maternal deaths and 10 cases of fetal death in utero. Conclusion: Obstetric ARF remains a serious complication of pregnancy for mother and child. It should be noted that hemodialysis was not accessible to all patients who were entitled to it due to lack of financial means. Therefore, regular monitoring of pregnancies should be prioritized, and, if possible, ensure that hemodialysis sessions are funded.